Integrating Technology in Primary Curriculum Development: Improving the Quality of Education - Ikrianibangga; Cici Fatmasari; Sriwindari Supit; Sri Atika Sudarto; Fitriyani Daud; Septiani Sanustika Suleman; Melani Samau; Indri Oktaviani To’onau; Elvia Rahmawati Hippy; Marsellad.Gui (International Journal of Advanced Technology and Social Sciences, 2023)
This article discusses the importance of technology integration in developing elementary school (SD) curricula to improve the quality of education. The strategy for improving the quality of education is to implement information technology in school learning. This implementation will support the learning process which produces students skilled in anticipating advances in science and technology. The method used in this study uses a library research method or approach, library research can be interpreted as a series of activities relating to methods of collecting library data, reading and recording and processing research materials